Humanae Vitae and Licit Contraception? - Coffey, Patrick J. (Philosophy & theology, 1988)
This paper critiques John Noonan’s recent attempt to show the compatibility of Humanae Vitae and contraception. Although Noonan’s arguments are rejected, an alternate approach for showing that sort of compatibility is explored.